Effectiveness of novel xylanases belonging to different GH families on lignin and hexenuronic acids removal from specialty sisal fibres. Issue 3 (5th July 2013) - Valenzuela, Susana Valeria; Valls, Cristina; Roncero, M. Blanca; Vidal, Teresa; Diaz, Pilar; Pastor, F.I. Javier
Abstract BACKGROUND The effectiveness of xylanases on lignin removal from pulps differs widely depending on the enzyme family, the type of pulp and the bleaching sequence among other factors. Xylanases can also reduce the presence of undesirable hexenuronic acids in the papermaking fibers. The performance of non‐commercial xylanases belonging to families GH10, GH30, GH30‐CBM35 and GH11, and of the multicomponent xylanase from Paenibacillus barcinonensis for lignin and hexenuronic acids removal from sisal (Agave sisalana) has been evaluated. RESULTS Sisal pulps were bleached by an XP sequence, where X denotes the enzyme treatment and P a hydrogen peroxide extraction stage. Kappa number, brightness, viscosity and hexenuronic acid content of samples were determined. Sugars released from sisal pulps, other non‐wood fibres and also eucalyptus fibres, by the treatment with xylanases were also analysed. The best results were obtained with the GH10 xylanase and with crude supernatants of P. barcinonensis, which produced a lignin removal of 23% and a reduction of 25% in the hexenuronic acid content of sisal pulps without a significant loss of viscosity. CONCLUSION The release of sugars in the effluents from the X stage applied to sisal correlated with the effectiveness of the xylanases tested. The xylan content of wood and non‐wood fibres, the type of xylan and its accessibility also had an influence on the xylanase activity on pulps. © 2013 Society of Chemical Industry